Testing Practices in the 21st Century - Developments and European Psychologists' Opinions - Evers, Arne (Array, 2012)
The main goal of the European Federation of Psychologists' Associations (EFPA)Standing Committee on Tests and Testing (SCTT) is the improvement of testing practices in European countries. In order to reach this goal, the SCTT carries out various actions and projects, some of which are described in this paper. To better inform its work, it decided to survey the opinions of professional psychologists on testing practices. A questionnaire of 33 itesm was administered to a sample of 12, 606 professional psychologists from 17 European countries. The questionnaire was based on, but not identical to, one used in 2000. The new data show that the positive attitude of the respondents toward the use of tests that was obtained in 2000 has increased in most countries, with a high percentage of the surveyed psychologists using tests regularly. Five main dimensions explained 43% of the total item variance. The dimensions involve items relating to: Concern over incorrect test use, regulations on tests and testing, Internet testing, appreciation of tests, and knowledge and training relating to tests and test use. Important differences between countries were found on these five dimensions. Differences were found according to gender for four of the five dimensions and in relation to field of specialization for all five dimensions. The most commonly used tests are the classic psychometric tests of intelligence and personality: WISC, WAIS, MMPI, RAVEN, 16PF, NEO-PI-R, BDI, SCL-90. Finally, some future perspectives are discussed.